A Partial Least Square Approach to Predict Direct and Indirect Effects of Personality Traits, Aggressive Driving and Accident Proneness: An Integrated Safety and Logistics Framework - Muhammad Asyraf Mohd Kassim; Suhaila Abdul Hanan; Muhammad Safizal Abdullah; Ahmad Bashir Aziz; Chan Pei Hong (International Journal of Supply Chain Management, 2020)
Accident Proneness is still a new concept in road safety studies in Malaysia. The study aims to examine the measurement model of personality traits, aggressive driving and accident proneness in a large sample of Malaysian licensed drivers. A further aim is to investigate both direct and indirect effects of personality traits and direct effects of aggressive driving on accident proneness. Data were collected using by-hand survey. Participants were 732 fully licensed motor vehicle drivers, including 490 males and 242 females who completed a questionnaire including the Five Factor Personality Traits, Aggressive Driving, items related to drivers’ accident records and demographic characteristics. The result of PLS-SEM analysis revealed satisfactory measurement model of five factor personality traits, aggressive driving and accident proneness with acceptable convergent and discriminant validity. The results further show that the personality traits of conscientiousness negatively relate to accident proneness and aggressive driving. Openness to experience and aggressive driving are positively related to accident proneness while agreeableness is negatively related to aggressive driving and neuroticism is positively related to aggressive driving. In addition, the results show that agreeableness, conscientiousness and neuroticism have indirect effects on accident proneness through aggressive driving.